A Critical Review of Fiqh (Islamic Jurisprudence) of Oil and Gas - Roohollah Kohan Hoosh Nejad; Mohammad Hossein Altamimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper reviews the book “Fiqh (Islamic Jurisprudence) of Oil and Gas”, and provides a critical view on the content of the book. The emphasis of the author for writing the book is to make the MA and PhD students of “Oil and Gas Law”, “Energy Law” and “Oil and Gas Contracts” and other interested people be familiar with basic concepts and foundations of “Fiqh (Islamic Jurisprudence) of Oil and Gas” and give them access to short and simple texts in this regard. Although the book has tried to fill the gap mentioned in the goal for writing the script, it has failed so far as chosen texts and their arrangement do not have a suitable relation with oil and gas law and contracts, and it seems that review and reorganization of the script in such a way that the reader can understand the relationship between the chosen texts and oil and gas law and contracts help to increase the coherence of the book.